พฤติกรรมตามแนวคิดการบริโภคที่ยั่งยืนของผู้ใช้รถยนต์ต่อการซื้อยางรถยนต์ในอำเภอเมืองเชียงใหม่ - ทวิภู ตันสว่างดำรงกุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aimed to study the behavior according to sustainable consumption concept of car users towards purchasing tires in Mueang Chiang Mai District. Questionnaires were used as the tool to collect data. Data was, then, analyzed by the use of descriptive statistics, consisting of frequency, percentage, and mean. Car users with sustainable consumption concept were mostly married male, aged of 35-44 years old, with Bachelor’s degree. They worked as self-employed and earned income at the amount of 20,001-30,000 Baht. According to the correlation analysis on general information of two groups of car users, the findings presented that the difference of age, education background and income correlated with both groups of consumers at the 0.05 level of statistical significance. The behavior of both groups of car users towards selecting shops to change tires, giving reason for selecting a shop to receive tire services from, and indicating number of tires to be changed in each time positively correlated with the sustainable consumption concept towards purchasing tires among these two groups of car users. According to the analysis of variance on the importance of influential factors towards purchasing tires in according to the sustainable consumption concept between two groups of car users, the findings showed that both groups of consumers: a group of consumer with the sustainable consumption concept and a group of general consumer, paid the importance to the following sub-factors differently: good road-holding ability, easy-to-control ability without gliding, silence and gentle feeling on driving, standard service, excellent automotive mechanic, modern and complete tools and devices, reasonable price to quality, availability of installment payment (AEON, First Choice, and etc.), convenient location where was near workplace/accommodation, availability of guest room with facilities such as Internet, drinking water, and coffee, free of charge for after sale services, and availability of product guarantee within the agreed period.